Entrepreneur as career choice among university graduates / Rachel Robbie and Jubaidah Mohd Salleh - Robbie, Rachel; Mohd Salleh, Jubaidah (2016)
This study aims to examine the factors that might affect the university graduates' decision towards taking entrepreneurship as their career choice. The sample consists of 120 university graduates in Kota Kinabalu area. A set of questionnaire has been used as a study instrument and data were analysed using Statistics Package for Social Science (SPSS) for Windows Version 18. Result shows that all the factors that been examine highly influence the university graduates' decision about taking entrepreneurship as their career choice is at high level. In addition, this study also finds that there is a positive and significant relationship between the influencing factors and the university graduates decision on choosing entrepreneurship field as their sources of income. In summary, the positive result on the influencing factors would make a person more likely to engage in entrepreneurial activities and have high intention in choosing this field as their main career choice. Implication of the study is that Higher Education Institutes should expose students to actual entrepreneurial activity as revealed in the early learning through their involvement in entrepreneurship activities during their study at their respective universities. Plus, the university graduates itself should taking into account on those internal and external factors as to boost their enthusiasm in choosing this field as their career. In addition, the element of innovation and risk control should be incorporated in entrepreneurship education in universities.